Reflexive Responsibilisierung Verantwortung für nachhaltige Entwicklung - Henkel, Anna; Lüdtke, Nico; Buschmann, Nikolaus; Hochmann, Lars (Sozialtheorie, 2018)
By using the term of responsibilization, this book poses the question about the attribution of responsibility and discusses the options and limitations of individual and collective responsibility for sustainable development.